Fenologia, adubação orgânica e micropropagação de acessos de sambaicaitá (Hyptis pectinata L. Poit) - Feitosa, Rosana Barroso (2013)
The medicinal plants have been widely used in recent decades for therapeutic, driven by the high cost of industrialized pharmaceutical products. Among the great diversity of medicinal plants found in Brazil, is the |sambacaitá| or |canudinho| (Hyptis pectinata L. Poit), which stands out for its wide use in the treatment of bacterial infections, pain and inflammation. The intense extraction of medicinal plants has made several species enter in extinction. Therefore it is necessary to understand the mechanisms of plants for adaptation of cultivation techniques and vegetative propagating that aim sustainability and large scale production. In this context, the aim of this work was to realize a phenologic study to evaluate the influence of cattle manure and cutting heights and establish a protocol for micropropagation of H. pectinata. For the phenology study we realized evaluations weekly on plants with and without irrigation. To evaluate the influence of cattle manure and cutting heights, the experiment was arranged in a randomized block design, using split plot scheme, placing cattle manure doses in the plots and cutting heights of plants in the in the split plots. In the micropropagation assays we tested different concentrations of growth regulators. Finally, for the acclimatization assay we tested different substrates containing coconut coir and / or vermiculite. For the conditions of the Sergipe State it was observed that the beginning of flowering of H. pectinata plants occurs in late July, that is the rainy season, that in early October occurs the seed dispersion and from late October the plants enter in senescence. It is noted that H. pectinata is an annual plant. H. pectinata supports three harvests and cutting at 20 cm from the ground resulted in better regrowth. The organic manure is not a limiting factor for the growth of H. pectinata. The accessions SAM-016, SAM-017 and SAM-018 of H. pectinata can be micropropagated in medium containing 50% of MS salts without using growth regulators. The acclimatization of plantlets can be performed in coconut coir substrate + 1g.L-1 of lime stone + MS salts.